Cardiotoxicities of novel cancer immunotherapies - Stein-Merlob, Ashley F; Rothberg, Michael V; Ribas, Antoni; Yang, Eric H (Heart (British Cardiac Society), 2021)
Immunotherapy revolutionised oncology by harnessing the native immune system to effectively treat a wide variety of malignancies even at advanced stages. Off-target immune activation leads to immune-related adverse events affecting multiple organ systems, including the cardiovascular system. In this review, we discuss the current literature describing the epidemiology, mechanisms and proposed management of cardiotoxicities related to immune checkpoint inhibitors (ICIs), chimeric antigen receptor (CAR) T-cell therapies and bispecific T-cell engagers. ICIs are monoclonal antibody antagonists that block a co-inhibitory pathway used by tumour cells to evade a T cell-mediated immune response. ICI-associated cardiotoxicities include myocarditis, pericarditis, atherosclerosis, arrhythmias and vasculitis. ICI-associated myocarditis is the most recognised and potentially fatal cardiotoxicity with mortality approaching 50%. Recently, ICI-associated dysregulation of the atherosclerotic plaque immune response with prolonged use has been linked to early progression of atherosclerosis and myocardial infarction. Treatment strategies include immunosuppression with corticosteroids and supportive care. In CAR T-cell therapy, autologous T cells are genetically engineered to express receptors targeted to cancer cells. While stimulating an effective tumour response, they also elicit a profound immune reaction called cytokine release syndrome (CRS). High-grade CRS causes significant systemic abnormalities, including cardiovascular effects such as arrhythmias, haemodynamic compromise and cardiomyopathy. Treatment with interleukin-6 inhibitors and corticosteroids is associated with improved outcomes. The evidence shows that, although uncommon, immunotherapy-related cardiovascular toxicities confer significant risk of morbidity and mortality and benefit from rapid immunosuppressive treatment. As new immunotherapies are developed and adopted, it will be imperative to closely monitor for cardiotoxicity.